Problematika Pembelajaran Daring Pelajaran Matematika di SMAN 1 Pejagoan Kabupaten Kebumen - Nurul Izza Kamila; Fadhilah Rahmawati; Selvi Yulia Wisudawati; Hanik Umi Khulasoh; Ani Kurnia Lestari; Sandri Yulia Rahma (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
The purpose of this study was to find out what problems students faced in learning mathematics online during the Covid-19 pandemic. This type of research is qualitative research. The subjects of this study were students of class XII SMAN 1 Pejagoan. The data collection instrument used was a questionnaire or electronic questionnaire in the form of Google form. The Google form measurement scale used is a Likert scale consisting of Strongly Agree (SS), Agree (S), Disagree (TS), Strongly Disagree (STS). Samples were taken randomly, in order to get 60 respondents.